Pemaknaan Will to Crime Karakter Raskolnikov pada Novel Kejahatan dan Hukuman Karya Fyodor Dostoyevsky - Farhan Heri Yasin; Supriyono B. Sumbogo (Epistemik Press, 2020)
Crime and its depiction are closely related to the narrative context, especially literary works in the form of novels. Detective/criminal novels specialize in depicting crimes. Fyodor Dostoyevsky's novel Crime and Punishment specifically describes the crime of murder committed by Raskolnikov's character in the story. The complexity of the will to crime formation experienced by Raskolnikov is a problem that is driven and causes instinctive behavior to commit the act of execute will to crime to commit to crime. In this study, the authors use the perspective of Existential Philosophy and the techniques of neutralization Sykes and Matza using qualitative research methods and content analysis approaches. The results of this study conclude that in 4 (four) phases that have been categorized as conflict and depictions of execution of will to crime found 5 (five) forms of neutralization by Raskolnikov as the self executing will to crime into commit to crime and 6 (six) depictions of the self, they, and the form of responsibility to the self.